Review the Legal Subject Status of Buyers in Underhand Sales of Mortgage Objects - Fahrul Fauzi (Jurnal Hukum Prasada, 2023)
The Mortgage Law regulates three types of execution of mortgage rights, namely Title Executorial, Parate Execution, and Underhand Execution. In the underhand execution, it is important to pay attention to the buyer's legal subject of the mortgage's object. This article examines the buyer's legal subject of the mortgage's object in underhand sales in the framework of the execution of the mortgage. The buyer's legal subject is important, considering that the national land law stipulates that the status of the land determines the status of the subject who can own it. This study uses normative juridical research methods using sources of legislation and other secondary legal materials. This study found that the underhand execution of the mortgage object must be carried out by considering the legal conditions of buying and selling land, both material and formal. Material requirements in the form of the importance of the legal subject status of a land buyer are essential things that need attention. If the material requirements are not met, the sale and purchase are null and void by law. The legal subject status of the buyer of the mortgage object must see the provisions in the Basic Agrarian Law or its derivative provisions to ensure that he has the right to hold land with the status of the rights in question.